Fire protection of steel members with intumescent coatings - Mesquita, L.M.R. (2018)
This work presents a set of 50 experimental fire resistance tests made in a pilot gas furnace and considering: (i) different member cross-sections (IPE, SHS, CHS, LNP), (ii) analysis at ambient temperature and fire conditions, (iii) application of a mechanical loading in a tree-point bending setup, (iv) different utilization degree level (30%, 50%, 70%) and (v) different intumescent thicknesses. Results show that increasing intumescent fire protection thickness an increase in fire resistance time is achieved. For the same nominal protection thickness the critical temperature and fire resistance time decreases with increasing degree of utilisation. The results from the unprotected fire tests are compared with the ones obtained by the Eurocode 3 part 1.2 simplified calculation method. Taking into account the nominal properties only the CHS section experimental results shows unsafe fire resistance times in comparison to the Eurocode values.